SOSIALISASI PENGEMBANGAN MANAJERIAL KELOMPOK UMKM DAN PEMASARAN PRODUK - Hariyadi, Rizki Hariyadi; Jufrin; Yulita, Sulistia Ilma; Supiati; Muhajirin; Mujahidin, Muhammad Ilham; Cahyani, Mega; Siskawati; Rakien, M. Aryabin Adzqia; Adha, Dia’ul (Universitas Mataram, 2024)
In the current era of globalization, MSMEs must increase the speed of thinking related to creativity and innovation on an ongoing basis. This process includes continuous product development, promotion, and productive. Socialization of product managerial and marketing of MSME products is very important in driving their business growth. Managerial is important for MSME owners so that they understand well how to manage their business. This socialization itself has a role in addition to managerial improvement and also aims to improve and provide understanding to MSME players in marketing their products in today's modern era. The implementation of this activity was held on Tuesday, January 23, 2024 at the Labuhan Pandan Village Office Hall, Sambelia, East Lombok. The KKN PMD program in Labuhan Pandan Village took place from December 2023 - February 2024. This socialization activity was carried out to be able to provide new understanding and learning for MSME players in Labuhan Pandan Village. We carried out socialization or counseling related to MSMEs on January 23, 2024 at the Labuhan Pandan Village Office Hall. This activity also invited MSME players by bringing processed products from each group. In addition, an understanding is given regarding the importance of having a halal label for a product. So that it is given an understanding that it is important to make NIB and SPP-IRT to be one of the requirements from BPOM to accept the halal label